Reports of Currency Committees - Planning Commission (Planning Commission, 1981)
The question referred to the Committee by Your Lordship is whether, having regard to the grave difficulties with which the Government of India are confronted through the heavy fall in the gold value of silver, it is expedient that Her Majesty’s Government should allow them to carry into effect the proposals which they have made for stopping the free coinage of silver in India with a view to the introduction of a gold standard. And if we are of opinion that there is no sufficient ground for overruling the Government of India, but that the measures by which they propose to attain their object require modification, we are asked to offer any suggestion that we think fit for the purpose.
Government of India
Government of India